Antiplatelet Therapy: Aspirin Resistance and All That Jazz!. (January 2013) - Divani, Afshin A.; Zantek, Nicole D.; Borhani-Haghighi, Afshin; Rao, Gundu H. R.
Platelets play a crucial role in the pathogenesis of atherosclerosis, thrombosis, and stroke. Aspirin used alone or in combination with other antiplatelet drugs has been shown to offer significant benefit to patients at high risk of vascular events. Resistance to the action of aspirin may decrease this benefit. Aspirin resistance has been defined by clinical and/or laboratory criteria; however, detection by laboratory methods prior to experiencing a clinical event will likely provide the greatest opportunity for intervention. Numerous laboratory methods with different cutoff points have been used to evaluate the resistance. Noncompliance with aspirin treatment has also confounded studies. A single assay is currently insufficient to establish resistance. Combinations of results to confirm compliance and platelet inhibition may identify "at-risk" individuals who truly have aspirin resistance. The most effective strategy for managing patients with aspirin resistance is unknown; however, studies are currently underway to address this issue.